Elevated carbon dioxide enhances the growth and reduces the antifungal susceptibility of Histoplasma capsulatum - Qian Shen; Kelsey Steinmetz (Microbiology Spectrum, 2025)
ABSTRACT Histoplasma capsulatum is a thermally dimorphic fungal pathogen. It causes approximately 500,000 infections annually in the United States. Histoplasma is present as avirulent mycelia in the soil and transforms into pathogenic yeasts at the human body temperature upon inhalation. This elevated temperature triggers the expression of many virulence factors that enable Histoplasma yeasts to survive and proliferate within immune cells (i.e., macrophages) in the human lungs. In addition to elevated temperature, Histoplasma yeasts also experience other environmental changes within the mammalian host, such as elevated carbon dioxide (CO2) (ambient air vs host tissues) during infection. However, the impact of elevated CO2 on Histoplasma yeasts remains completely unknown. In this study, our results showed that elevated CO2 enhanced Histoplasma’s growth, particularly increasing its ability to utilize certain amino acids (e.g., alanine) as the sole carbon source. We also found that elevated CO2 reduced Histoplasma’s susceptibility to antifungals in vitro. Histoplasma’s enhanced growth and reduced antifungal susceptibility under elevated CO2 were not pH-dependent. Our findings suggest that the elevated CO2 within mammalian hosts could potentially enhance Histoplasma’s virulence. Future antifungal susceptibility tests for Histoplasma should be performed at 5% CO2 for clinically relevant results.IMPORTANCEThe fungal pathogen Histoplasma capsulatum lives in the soil. Histoplasma spores can be inhaled and cause respiratory infections. The human body is vastly different from the soil. One of the major differences is the carbon dioxide (CO2) concentration (0.04% in the ambient air vs 5% or above in the human body). Therefore, it is important to understand the impact of elevated CO2 on Histoplasma. We found that elevated CO2 promotes Histoplasma’s growth, suggesting that elevated CO2 could potentially enhance Histoplasma’s virulence during infection. Our results showed that elevated CO2 reduces Histoplasma’s antifungal susceptibility, suggesting that antifungal susceptibility tests for Histoplasma should be performed at elevated CO2 for clinically relevant results.